Templated insertions at VD and DJ junctions create unique B‐cell receptors in the healthy B‐cell repertoire. Issue 12 (27th August 2020) - Koning, Marvyn T.; Vletter, Esther M.; Rademaker, Rik; Vergroesen, Rochelle D.; Trollmann, Ignis J.M.; Parren, Paul; van Bergen, Cornelis A.M.; Scherer, Hans U.; Kiełbasa, Szymon M.; Toes, René E.M.; Veelken, Hendrik
Abstract : RAG complexes recognise (cryptic) RSS sites both in and outside immunoglobulin sites. Excision circles may be reinserted into V(D)J rearrangements as long templated insertions to diversify the adaptive immune repertoire. We show that such VDJ with templated insertions are incidentally found in the repertoire of healthy donors.